Decidual polyps are associated with preterm delivery in cases of attempted uterine cervical polypectomy during the first and second trimester. (30th July 2014) - Tokunaka, Mayumi; Hasegawa, Junichi; Oba, Tomohiro; Nakamura, Masamitsu; Matsuoka, Ryu; Ichizuka, Kiyotake; Otsuki, Katsufumi; Okai, Takashi; Sekizawa, Akihiko
Abstract: Objective : To clarify which types of cervical polyp removed during the first and second trimester are associated with the risk of spontaneous abortion and preterm delivery. Methods : Pregnant females who underwent attempted polypectomy of cervical polyps during pregnancy and delivered singleton infants between 2005 and 2011 were evaluated. The clinical courses and outcomes of preterm delivery after polypectomy stratified according to the pathologic diagnosis of the polyps were retrospectively reviewed. The removed polyps were classified into decidual polyps and endocervical polyps. Results : The pathological diagnoses included 41 decidual polyps and 42 endocervical polyps. No malignant polyps were found. The removal of decidual polyps during pregnancy carried a higher risk of spontaneous abortion (12.2% versus 0%, p = 0.026) and preterm delivery (34.2% versus 4.8%, p = 0.001) than that of endocervical polyps. According to the multivariate logistic regression analysis, risk factors for preterm delivery before 37 weeks' gestation were the presence of decidual polyps and a history of preterm delivery. Conclusions : The risk of abortion and preterm delivery associated with polypectomy during pregnancy is greater in patients with decidual polyps. It might be safer not to remove cervical polyps during pregnancy, except in cases in which the polyps are suspected to be malignant.